Connect MDS/AML: design of the myelodysplastic syndromes and acute myeloid leukemia disease registry, a prospective observational cohort study. Issue 1 (December 2016) - Steensma, David; Abedi, Medrdad; Bejar, Rafael; Cogle, Christopher; Foucar, Kathryn; Garcia-Manero, Guillermo; George, Tracy; Grinblatt, David; Komrokji, Rami; Ma, Xiaomei; Maciejewski, Jaroslaw; Pollyea, Daniel; et al.
Abstract Background Myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) are myeloid neoplasms in which outgrowth of neoplastic clones disrupts normal hematopoiesis. Some patients with unexplained persistent cytopenias may not meet minimal diagnostic criteria for MDS but an alternate diagnosis is not apparent; the term idiopathic cytopenia of undetermined significance (ICUS) has been used to describe this state. MDS and AML occur primarily in older patients who are often treated outside the clinical trial setting. Consequently, our understanding of the patterns of diagnostic evaluation, management, and outcomes of these patients is limited. Furthermore, there are few natural history studies of ICUS. To better understand how patients who have MDS, ICUS, or AML are managed in the routine clinical setting, the Connect MDS/AML Disease Registry, a multicenter, prospective, observational cohort study of patients newly diagnosed with these conditions has been initiated. Methods/Design The Connect MDS/AML Disease Registry will capture diagnosis, risk assessment, treatment, and outcomes data for approximately 1500 newly diagnosed patients from approximately 150 community and academic sites in the United States in 4 cohorts: (1) lower-risk MDS (International Prognostic Scoring System [IPSS] low and intermediate-1 risk), with and without del(5q); (2) higher-risk MDS (IPSS intermediate-2 and high risk); (3) ICUS; and (4) AML in patients aged ≥ 55 years (excluding acute promyelocytic leukemia). Diagnosis will be confirmed by central review. Baseline patient characteristics, diagnostic patterns, treatment patterns, clinical outcomes, health economics outcomes, and patient-reported health-related quality of life will be entered into an electronic data capture system at enrollment and quarterly for 8 years. A tissue substudy to explore the relationship between karyotypes, molecular markers, and clinical outcomes will be conducted, and is optional for patients. Discussion The Connect MDS/AML Disease Registry will be the first prospective, observational, non-interventional study in the United States to collect clinical information, patient-reported outcomes, and tissue samples from patients with MDS, ICUS, or AML receiving multiple therapies. Results from this registry may provide new insights into the relationship between diagnostic practices, treatment regimens, and outcomes in patients with these diseases and identify areas for future investigation. Trial registration Connect MDS/AML Disease Registry (NCT01688011 ). Registered 14 September 2012.